Eucharistic celebrations: the chasm between idea and action - O'Loughlin, Thomas (Wiley, 2009)
The two changes (1, a new rite; and 2. the move to the vernacular) that occurred in the eucharistic liturgy of the Roman Rite have often been seen as simply evolutionary, liturgical variations: this perception suited that time of great change in the liturgy, and has continued among many in that they assume that these changes are somehow optional. However, this change is better seen as a change in paradigm: no longer is the general understanding of the Eucharist based in catechesis or theology that is parallel to the liturgy, but the understanding of the Eucharist is a function of participating linguistically in the actual event of the Eucharist. This paradigm shift needs to be appreciated if we are to discuss the state of eucharistic theology and liturgical celebration today.